Pathogenesis of sarcopenia in chronic obstructive pulmonary disease - Ma, Kai; Huang, Fengxiang; Qiao, Ruiping; Miao, Lijun (Frontiers in Physiology, 2022)
Chronic obstructive pulmonary disease (COPD) is a common pulmonary disease characterized by persistent respiratory symptoms and airflow obstruction. In addition to lung diseases, chronic obstructive pulmonary disease (COPD) is often associated with other organ diseases, and sarcopenia is one of the common diseases. In recent years, multiple factors have been proposed to influence muscle dysfunction in COPD patients, including systemic and local inflammation, oxidative stress, hypoxia, hypercapnia, protein synthesis, catabolic imbalance, nutritional changes, disuse, ageing, and the use of medications such as steroids. These factors alone or in combination can lead to a reduction in muscle mass and cross-sectional area, deterioration of muscle bioenergy metabolism, defects in muscle repair and regeneration mechanisms, apoptosis and other anatomical and/or functional pathological changes, resulting in a decrease in the muscle’s ability to work. This article reviews the research progress of possible pathogenesis of sarcopenia in COPD.